The essential role of phospho‐T38 CPI‐17 in the maintenance of physiological blood pressure using genetically modified mice. Issue 4 (5th January 2018) - Yang, Qunhui; Fujii, Wataru; Kaji, Noriyuki; Kakuta, Shigeru; Kada, Kodai; Kuwahara, Masayoshi; Tsubone, Hirokazu; Ozaki, Hiroshi; Hori, Masatoshi
Abstract : PKC‐potentiated phosphorylation‐dependent inhibitory protein of protein phosphatase 1 (CPI‐17), an endogenous myosin phosphatase inhibitory protein, is considered a key molecule for Ca 2+ sensitization of the contractile apparatus. Here, we have used clustered regularly interspaced short palindromic repeats (CRISPR)/ CRISPR‐associated protein 9 to generate CPI‐17‐deficient [knockout (KO)] and threonine 38 (T38)‐phosphoresistant mice [threonine mutant into alanine (TA)], and then effects of CPI‐17 on vascular contractility in vitro and mean blood pressure (MBP) in vivo were investigated. In isolated thoracic aorta, phorbol 12, 13‐dibutyrate induced a sustained contraction of wild‐type (WT) mice, whereas no contraction showed from TA or KO mice. A high concentration of KCl solution‐induced contraction was not different between transgenic and WT mice. In contrast, phenylephrine (PE)‐induced contractions in both mutant strains were significantly smaller than those of WT mice in association with a low level of myosin phosphorylation, suggesting that at least part of PE‐induced contraction is regulated by phosphorylation of CPI‐17 at T38. Finally, the physiologic role of CPI‐17 in the regulation of blood pressure was investigated using radio telemetry. MBP was decreased significantly in both transgenic mice, even with a compensatory increase in heart rate. In summary, we generated KO and constitutively phospho‐resistant mouse models of CPI‐17 for the first time. p‐CPI‐17 at T38, possibly by PKC, could be important to maintain vascular contractility and blood pressure in vivo.— Yang, Q., Fujii, W., Kaji, N., Kakuta, S., Kada, K., Kuwahara, M., Tsubone, H., Ozaki, H., Hori, M. The essential role of phospho‐T38 CPI‐17 in the maintenance of physiological blood pressure using genetically modified mice. FASEB J. 32, 2095–2109 (2018). www.fasebj.org